Affordable telecommunications: A new digital economy is calling - Poblet, Marta (Journal of Telecommunications and the Digital Economy, 2019)
The unparalleled success of mobile technologies, the emergence of new modes of software and hardware production, and the free circulation of shared knowledge in the Web 2.0 have enabled a new generation of bottom-up, community-based, cost-effective telecommunications initiatives and projects. While these endeavours find their roots in previous hobbyists’ movements (i.e. amateur radio, software hackers, do-it-yourself communities) today's’ initiatives are able to connect, co-produce and share knowledge with world-wide communities, engaging new participants both at the local and the global level.This article reviews recent developments that aim to provide free or low-cost access to telecommunication services in different areas. From Do-It-Yourself (DIY) satellites to mesh networks, these projects tap into the wisdom and resources of communities to offer non-commercial alternatives to present telecommunications services. The technology, organisational, and regulatory challenges they also face cannot be underestimated either. However, in their struggle to find and consolidate new markets, affordable telecommunications reveal that a new digital economy based on co-production could be under way.